Testing Commodities as Safe Haven and Hedging Instrument on ASEAN's Five Stock Markets - Robiyanto, Robiyanto (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252)DO - 10.24843/JEKT.2017.v10.i02.p11, 2017)
This study attempts to analyze commodity market instruments such as gold, silver, platinum, palladium, and West Texas Intermediate (WTI) crude oil’s potential as hedge and safe haven toward some stock markets in South East Asia such as in Indonesia, Singapore, Malaysia, Philippines, and Thailand. To analyze the data, GARCH (1,1) was applied. The research findings showed that gold, silver, platinum, palladium, and WTI could not play their role as hedging instrument for five South East Asian capital markets. WTI could act as a robust safe haven for most South East Asian capital markets. Gold could do the role as a robust safe haven in Singapore and Malaysia, whereas, platinum and silver consistently could be safe haven only for Singapore Stock Exchange. Palladium could only be safe haven for Philippines Stock Exchange.
Keywords: Safe Haven, Hedging, West Texas Intermediate, Precious Metals